Meningkatan Kesadaran Sosial dan Peran Aktif Pemuda dalam Membangun Komunitas Sosial Kepemudaan Di Desa Kalipecabean - Dhalia, Era Dinisiadela; Shofyuddin, Ahmad; Junian, Ivan Wahyu Arta; Cahyani, Nita Putri; Laura, Oidhia; Arum, Dewi Puspa (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The role of youth in community development is very important. The social awareness program implemented by Karang Taruna in Kalipecabean Village aims to overcome social challenges such as juvenile delinquency, violence, and drug abuse. This program is designed to increase youth involvement in positive and productive social activities through several important aspects such as: selection of qualified members of the Youth Organization, socialization about the dangers of juvenile delinquency, and leadership development. This method uses the Participatory Action Research method or commonly known as the PAR method in Kalipecabean Village which begins with observation through interviews with the head of Kalipecabean Village and the community to find out the problems that exist in relation to it. The results of the service show the success of rebuilding youth awareness in Kalipecabean Village. With this program, it is hoped that it can educate and motivate village youth to play an active role in the community and develop the skills needed to face social challenges.